2012
DOI: 10.1177/1350650112441747
|View full text |Cite
|
Sign up to set email alerts
|

Effects of off-sized cylindrical rollers on the static load distribution in a cylinder roller bearing

Abstract: There are always some differences in the diameters of the rolling elements that are less than manufacturing tolerance, which are known as off-sized defects. These diameter differences of the rolling elements assumed to be with identical size in the traditional bearing analysis affect the load performance of the bearing greatly and make the evaluation of the load distribution in the bearing difficult. In this study, a static model was developed to investigate the effects of diameter differences among cylindrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The vibration behaviors of the rotor roller bearing system were investigated. Chen et al 21,22 developed a one-dimensional model for calculating the radial runout considering roundness error of raceways and diameter error of the rollers and presented a static model for the load performance in a cylindrical roller bearing based on diameter error of the rollers. The effects of diameter differences among the rollers on the load performance and the radial runout in a cylindrical roller bearing are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The vibration behaviors of the rotor roller bearing system were investigated. Chen et al 21,22 developed a one-dimensional model for calculating the radial runout considering roundness error of raceways and diameter error of the rollers and presented a static model for the load performance in a cylindrical roller bearing based on diameter error of the rollers. The effects of diameter differences among the rollers on the load performance and the radial runout in a cylindrical roller bearing are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Noguchi 25 studied influences of balls' diameter differences on value of retainer revolution and showed that the mean value of the retainer revolution decreases as the number of balls increases in a rolling bearing. Chen et al 26 present a static model to investigate the effects of diameter differences among cylindrical rollers on the load performance in a bearing. In the same year, Chen et al 27 conducted further research to investigate the effect of raceway roundness and roller diameter errors on the radial clearance and runout of the bearing and found that clearance, and runout are greatly affected by the rollers' diameter errors rather than their positions.…”
Section: Introductionmentioning
confidence: 99%
“…where is the distance between any point on the inner raceway and the center of the th roller, which is calculated by (14).…”
Section: Contact Statuses Of the Inner Raceway In Different Positionsmentioning
confidence: 99%
“…Yang et al [10][11][12] established a mathematical model and a five-degree-of-freedom model to research the influences of geometric error on the NRRO of an angular contact ball bearing. Chen et al [13,14] developed a one-dimensional mathematical model with algebraic equation considering roundness error of the raceways and diameter error of the rollers. The influence of diameter differences among the rollers on the load performance in a cylindrical roller bearing was investigated.…”
Section: Introductionmentioning
confidence: 99%